Research on high-throughput detection of plasma cell-free DNA for targeted therapy-related genes screening and prognosis prediction in non-small cell lung cancer patients - DENG Qiling, SONG Di, XI Kexin, XIE Xiaoting, WU Xiaoyan, ZHAO Wei (Zhongguo aizheng zazhi)
Background and purpose: High-throughput detection of plasma cell-free DNA (cfDNA) is widely used for multi-cancer targeted therapy drug screening, and this study investigated the relationship between the type and number of plasma cfDNA class Ⅰ and Ⅱ targeted therapy-related gene variants and cancer survival in patients with non-small cell lung cancer (NSCLC). Methods: The sequencing results and clinical data of NSCLC patients who underwent tumor plasma cfDNA high-throughput sequencing projects in Sun Yat-sen University Cancer Center from 2021 to 2023 were collected. The survival follow-up of enrolled patients was carried out from the day of plasma collection on June 1, 2021 to May 27, 2024, and GraphPad Prism 8.0 and SPSS Statistics 25.0 were used. Univariate and multivariate statistical analyses were conducted on the types and numbers of class Ⅰ and class Ⅱ targeted therapy-related genes in the survival and clinical data of patients and sequencing results (Ethical approval: B2024-359-01). Results: A total of 313 patients included in this study with NSCLC were categorized into stage Ⅰ 25 patients (7.98%), stage Ⅱ 20 patients (6.39%), stage Ⅲ 38patients (12.14%), and stage Ⅳ 230 patients (73.48%). Pathological diagnosis results showed that adenocarcinoma accounted for 90.10%, squamous cell carcinoma accounted for 5.11%, large cell carcinoma accounted for 2.87% and other classifications accounted for 1.92%. The number and the percentage of class Ⅰ and class Ⅱ targeted therapy drug-related genes in the plasma cfDNA NSCLC patients were 0 (25.24%), 1 (17.57%), 2 (19.17%), 3 (14.38%), 4 (8.31%), and 5 or more (15.34%). The results of statistical analysis showed that 3 genes with the highest mutation frequencies were EGFR, TP53 and ERBB2, and the mutation frequency of EGFR gene was 36.04%. The mutation frequency of TP53 gene was 30.63%. The mutation frequency of ERBB2 gene was 4.95%. The survival time of patients is related to not only the expression of hotspot targeted genes, but also the number of class Ⅰ and Ⅱ target-related gene variants detected by plasma cfDNA high-throughput sequencing. The survival time of the patients with no targeted therapy-related locus variants after treatment was longer compares with targeted therapy-related locus variants, which can reduce the risk of death by 63.2%. However, patients with a single gene locus variant had longer survival time and lower risk of death than those with multiple driver locus variants, and the measured class Ⅰ and Ⅱ targeted therapy drugs were within 3 genes. Overall, the smaller the number of genes, the longer the survival. Conclusions: The number of class Ⅰ and class Ⅱ targeted therapy-related gene variants in plasma cfDNA high-throughput sequencing also has an effect on the survival of patients after treatment. Plasma cfDNA level detected by high-throughput sequencing could be a prognostic factor for the NSCLC patients.